The Attempts at Establishing a "Revolution Museum" During the Time of Atatürk - Betül Batır (Yakın Dönem Türkiye Araştırmaları)
During the beginning of preparations for the 10th anniversary of the Republic of Türkiye, political and intellectual circles proposed the idea of establishing a museum that would exhibit the 10-year course of the revolutions in Türkiye by taking advantage of the possibilities contemporary museology had brought to the agenda. Upon adopting this idea, attempts were initiated to establish a revolution museum, for which a Committee of Museums was formed. The committee was requested to have the Republic’s first 10 years of struggle depicted in the planned museum. The committee members were knowledgeable about history and museology but had different ways of viewing the idea of the revolution. The desire was to also have the Revolution Museum be created similar to the Ankara People’s House. This study discusses the efforts at establishing the Revolution Museum thathad been designed to be established in 1933 based on its counterparts in Russia, Germany, and Italy as well as the various arguments and opinions concerning the museum and the reasons for why it had failed. The subject and focus of this study are the Revolution Museum. The article mainly used the archival documents of the period, newspaper and journal news, and the minutes from Parliament in its writing, while also examining other sources.